2010
DOI: 10.1111/j.1365-2354.2008.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Hodgkin and non-Hodgkin patients at a greater risk of atherosclerosis? A follow-up of 3 years

Abstract: Aims and background are to ascertain whether Hodgkin and non-Hodgkin patients are more affected by atherosclerotic process. We studied 96 patients during a period of 3 years (2003-2007). Patients were assessed in the first year soon after receiving radiotherapy and chemotherapy and then reassessed in the third year. All the cases underwent echo-colour Doppler of the carotid axis, and the intima-media thickness (IMT) was measured. When the two time points were compared, the IMT was greater in the arterial distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…Also, Graus et al proposed that, the minimal dose for RT induced damage of the cervical arteries was assumed to be 41 Gy [16]. Bilora et al showed increased IMT of the arterial wall in Hodgkin and non-Hodgkin patients received RT compared to matched controls [17] [18]. Gianocolo et al confirmed these findings on 19 patients received neck irradiation and most of them had Hodgkin disease.…”
Section: Discussionsupporting
confidence: 71%
“…Also, Graus et al proposed that, the minimal dose for RT induced damage of the cervical arteries was assumed to be 41 Gy [16]. Bilora et al showed increased IMT of the arterial wall in Hodgkin and non-Hodgkin patients received RT compared to matched controls [17] [18]. Gianocolo et al confirmed these findings on 19 patients received neck irradiation and most of them had Hodgkin disease.…”
Section: Discussionsupporting
confidence: 71%
“…Recently, irradiation of the neck has been associated with subsequent vascular wall thickening [18], accelerated atherosclerotic plaque formation [19], decreased flow on ultrasound [20], and coronary artery stenosis [21]. A recent study found that irradiation of the neck of Hodgkin (H) and non-Hodgkin (NH) patients determines a greater IMT of the arterial wall than in controls matched for the classic atherosclerosis risk factors, so authors concluded that radiotherapy can influence the atherosclerotic process [22,23]. …”
Section: Discussionmentioning
confidence: 99%
“…During a 3-year followup, it was noted that despite improvement in intima-media thickens at 3 years, there was persistently reduced flow-mediated dilatation in the irradiated carotid artery, suggesting that early endothelial damage persists [47]. Radiation-induced carotid disease differs from traditional carotid disease.…”
Section: Radiation-induced Carotid Artery Diseasementioning
confidence: 99%